RESPONSE OF BROILER CHICKS TO DIETS CONTAINING GRADED LEVELS OF CLAY - `A. O. Ani; C.C. Ogbu; E.A. Iloh (Journal of Animal and Plant Sciences, 2014)
A total of 360 two weeks old broiler chicks were used to investigate the effect of varying dietary levels of clay on growth performance of broiler chicks. The birds were randomly divided into six groups of 60 birds each and the groups were randomly assigned to six diets containing six levels (0, 1, 2, 3, 4 and 5%) of clay. Each treatment was replicated two times with 30 birds per replicate. The study lasted for four weeks. The response parameters studied were body weight, feed intake, body weight gain, feed conversion ratio and protein efficiency ratio. Results showed that dietary clay inclusion significantly (P<0.05) improved weight gain and efficiency of feed utilization. There was significant (P<0.05) reduction in feed cost per kg weight gain and overall cost of production. The results indicated that up to 5% clay may be included in the diet of broiler chicks to enhance growth performance and to reduce the cost of production.
Keywords: Arbor Acre; feed conversion ratio; feed intake; growth performance